1988
DOI: 10.1111/j.1651-2227.1988.tb10725.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Electrocardiograms of Healthy Fullterm and Premature Newborns

Abstract: The electrocardiograms of 421 healthy fullterm and premature newborns, recorded on the fifth day of life, were evaluated for possible systematic differences related to gestational age. All newborns were appropriate for gestational age and were divided into four groups according to birthweight. As birthweight increased, we noted: (a) a progressive rightward shifting of the QRS axis in the frontal plane; (b) an increase in the amplitude mainly of the precordial R and S waves reflecting the right ventricle and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
2
5
0
1
Order By: Relevance
“…The average birthweight may differ between the cooperating centres, as it depends on the sex of the infant, the ethnic group of the mother, smoking, high altitude and many other factors 11 . A positive relationship between birthweight and the durations of the P‐wave and the QRS complex was also found in a study of immature newborns 12 .…”
Section: Discussionsupporting
confidence: 58%
“…The average birthweight may differ between the cooperating centres, as it depends on the sex of the infant, the ethnic group of the mother, smoking, high altitude and many other factors 11 . A positive relationship between birthweight and the durations of the P‐wave and the QRS complex was also found in a study of immature newborns 12 .…”
Section: Discussionsupporting
confidence: 58%
“…Newer imaging data [21] showed that the indexed mass of the left ventricle in GA weeks 29 to 37 de- clined more rapidly than the mass of the right ventricle consistent with a transition from LV dominance toward RV dominance. These findings of initial LV dominance changing to RV dominance toward term have been previously reported [22][23][24] although some discrepancies exist [25]. However, the anatomical and hemodynamic changes after birth are well described [4,22] and consistently show a switch toward LV dominance reflecting the transition from neonatal circulation with closure of the ductus arteriosus and foramen ovale as well as marked changes in pulmonary hemodynamics.…”
Section: -28 Dayssupporting
confidence: 63%
“…Fetal electrocardiographic studies show that the progressive increase in the QRS duration (with advancing gestation) parallels the gain in the weight of the fetal heart (Brambati and Pardi, 1980;Morgan and Symonds, 1991). A positive correlation between birthweight and duration of the P wave and QRS complex was also found in a study of premature newborns (Thomaidis et al, 1988). In addition, fECG and fMCG studies on fetuses with IUGR (presumably with smaller-sized hearts) have demonstrated a decrease in the PR interval (Van Leeuwen et al, 2001) as well as QRS width (Pardi et al, 1986).…”
Section: Discussionmentioning
confidence: 74%